P17 Acetylcholinesterase inhibitors for schizophrenia. Issue 10 (7th September 2012) - Singh, J; Kour, K; Jayaram, M
Abstract : Objective: The Acetylcholinesterase inhibitors (Donepezil, Rivastigmine and Galantamine) have been studied in the cognitive deficit states like Alzheimer's and others and have been in use for some time. These new group of compounds are being tried in the treatment of schizophrenia, there are no existing systematic reviews of these groups of compounds and there is an urgent need to critically examine the available evidence to find out whether it is worth considering these medications as an option either first line or second line in the treatment of schizophrenia. Method: We included all clinical randomised trials comparing acetylcholinesterase inhibitors with antipsychotics or placebo either alone or in combination for schizophrenia and schizophrenia-like psychoses. The outcomes were grouped into the short term (up to 12 weeks), medium term (13–26 weeks) and long term (over 26 weeks). Primary and secondary outcomes: The Primary outcome was improvement in global state and the secondary outcomes included: clinical global response, mental state, general functioning, quality of life/satisfaction with treatment, cognitive functioning, service use, adverse effect, economic outcomes, behaviour and engagement with services. Search strategy: We searched the Cochrane Schizophrenia Group Trials Register (February 2009). This register is compiled by systematic searches of major databases, hand searches and conference proceedings. The authors of significant papers were identified and were contacted and asked for their knowledge of other studies, published or unpublished, relevant to the review. The relevant pharmaceutical companies were requested to provide relevant published and unpublished data regarding any studies they may have access to. Data collection and analysis: Two review authors (JS and KK) independently inspected citations identified from the search. Authors (JS and KK) independently extracted data from included studies. Data were extracted onto standard, simple forms. Again (JS and KK) worked independently to assess risk of bias by using criteria described in the Cochrane Collaboration Handbook. Where possible, efforts were made to convert outcome measures to dichotomous data. We calculated the RR and its 95% CI based on the random-effects model. For continuous outcomes we estimated a Mean Difference (MD) between groups. Results: The acetylcholinesterase inhibitor plus antipsychotic showed benefit over antipsychotic and placebo in the following outcomes: (1) Mental state—PANSS negative symptoms average end point score (2 RCTs, n=31, WMD −1.69, CI −2.80 to −0.57), PANSS General Psychopathology average end point score (2 RCTs, n=31, WMD −3.86 CI −5.40 to −2.32) and improvement in depressive symptoms as measured by CDSS scale—one study. (2) Cognitive domains—attention, (1 RCT, n=73, MD 1.20, CI 0.14 to 2.26), visual memory (2 RCTs, n=48, MD 1.90, CI 0.52 to 3.28), verbal memory and language (3 RCTs, n=42, MD 3.46, CI 0.67 to 6.26) and executive functioning (1 RCT, n=24, MD 17.10, CI 0.70 to 33.50). (3) Tolerability—EPSE: AIMS, (1 RCT, n=35, MD 1.50 CI 1.04 to 1.96). No difference was noted between the two arms in other outcomes. The overall rate of participants leaving studies early was low (13.6 %) and showed no clear difference between the two groups. Conclusion: Current available evidence is not good enough for recommending acetylcholinesterase inhibitors routinely as add on intervention along with antipsychotics to improve efficacy or cognitive symptoms in those suffering from schizophrenia. It could perhaps be tried when all other interventions have failed, but its effects need to be assessed and treatment withdrawn if no evidence of any clinical benefit. Most of the studies were short-term studies and were not of high quality. It is therefore essential that longer term, better reported more pragmatic trials are needed before the evidence could be assessed objectively to conclude whether this intervention would be of benefit to patients or not.